2019
DOI: 10.3390/su11061750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Zero-Emission Vehicle Deployment Strategies: The Maryland Case

Abstract: This study aimed to develop a model to estimate the impacts of zero-emission vehicle (ZEV) adoption on CO2 emissions and to evaluate efficacy of ZEV deployment strategies in achieving greenhouse gas (GHG) emission reduction goals. We proposed a modeling scheme to represent ZEVs in four-step trip-based travel demand models. We then tested six ZEV scenarios that were a cross-combination of three ZEV ownership levels and two ZEV operating cost levels. The proposed modeling scheme and scenarios were implemented on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The model they used proved that policy can help reduce GHG emitted. Wang et al [19] used a four-step model to forecast trip behaviour in Maryland. The authors found that a high EV ownership scenario (43.14% of the fleet is made of EVs) would reduce CO 2 emissions by 16% from 2015 levels and would result in more balanced geographical distribution of emissions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model they used proved that policy can help reduce GHG emitted. Wang et al [19] used a four-step model to forecast trip behaviour in Maryland. The authors found that a high EV ownership scenario (43.14% of the fleet is made of EVs) would reduce CO 2 emissions by 16% from 2015 levels and would result in more balanced geographical distribution of emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Some work has been done to try to translate government policies or emission reduction strategies into changes in fleet or travel behaviour and see the associated impacts on CO 2 emitted [8,[17][18][19][20]22]. Article by Zahabi et al [22] studied the transition to hybrid buses, electric trains, or more fuel efficient cars and compared these strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation